Analysis of Factors Influencing Labor Absorption in ASEAN-4 Countries - Zhafirah, Rahma; Bachtiar, Arief (Universitas Gorontalo, 2026)
This study aims to analyze the factors influencing labor absorption in four ASEAN countries—Indonesia, Malaysia, Thailand, and the Philippines—during the period 2014–2023. The variables used include the Global Innovation Index (GII), Gross Enrollment Ratio (GER), minimum wage, and Foreign Direct Investment (FDI). The research method used is a quantitative approach with panel data regression analysis using a fixed effects model. The results show that the Global Innovation Index has a significant negative effect on labor absorption, indicating that increased innovation and technology can reduce the demand for traditional labor. Conversely, the Gross Enrollment Ratio (GER) and minimum wage have a significant positive effect, indicating that increased educational participation can improve the quality of human resources and expand employment opportunities. Meanwhile, Foreign Direct Investment (FDI) has no significant effect on labor absorption in ASEAN-4 countries. This study emphasizes the importance of improving the quality of education and digital skills of the workforce so that innovation and investment can drive more inclusive and sustainable job creation in the ASEAN-4 region.